Peran Pengungkapan Akuntansi Lingkungan pada Stock Return di Perusahaan GO Publik di Indonesia 2021-2024 - Alda Lorenza; Repaldo Repaldo; Dzakira Isratun Nisa (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the role of environmental accounting disclosure on stock returns of publicly listed companies in Indonesia. Growing awareness of environmental issues has encouraged companies to focus not only on financial performance but also on transparency regarding the environmental impacts of their operations. Environmental accounting disclosure represents a form of corporate responsibility that provides relevant information for stakeholders, particularly investors, in assessing business sustainability.This research applies a systematic literature review using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) approach. The reviewed articles consist of empirical studies published between 2021 and 2025 that are relevant to environmental accounting disclosure and stock returns. Data were collected through Google Scholar using specific keywords, and selected articles were further analyzed to identify research patterns and consistency of findings.The results indicate that environmental accounting disclosure does not have a significant effect on stock returns of publicly listed companies in Indonesia. This finding is influenced by several factors, including investors’ tendency to prioritize short-term financial gains, while environmental information is generally long-term oriented. In addition, environmental disclosure practices in Indonesia remain voluntary, resulting in variations in disclosure quality and completeness across companies. Consequently, such information has not been able to consistently influence investment decisions. The findings suggest that although environmental accounting disclosure plays an important role in supporting corporate sustainability, its impact on stock returns remains limited.